International education policymaking: A case study of Ontario’s Trillium Scholarship Program - El Masri, Amira (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
This paper explores Ontario’s international education policy landscape through illuminating the discursive struggles to define international student funding policies, in particular the international doctoral students’ Trillium Scholarship. Adopting Hajer’s (1993, 2006) Discourse Coalition Framework, the study engages with three research questions: What paved the way to this funding policy? Who were the actors engaged in this policy landscape? How has the argumentation over this policy influenced the international education policy context in Ontario? Argumentative discourse analysis was used to analyze three data sources: news articles, policy documents, and interviews. Two storylines were identified: international student funding is desirable and beneficial to Ontario versus Ontario first. Whereas the first storyline achieved hegemony, the second succeeded in bringing discourses of protectionism to the forefront influencing the government’s future engagement with international student funding. The paper ends with three observations on Ontario’s international education policy landscape. This study contributes to our understanding of how international student funding can be highly political and influenced by non-education policy spaces and discourses.